2004
DOI: 10.1038/sj.eye.6701622
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic vitreopapillary traction and macular oedema

Abstract: Purpose To describe an association between optic disc traction and diabetic macular oedema (DME) unresponsive to laser treatment. Methods A retrospective review of all patients with DME who attended our clinic between September 2001 and November 2003 was undertaken. The patients had undergone ophthalmic history and examination, fluorescein angiography, and optical coherence tomography (OCT) of the macular area and optic nerve head (ONH). A total of 10 nonvitrectomized eyes that were found to have an elevation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Extrafoveal traction sites are illustrated to be commonly associated with diffuse macular oedema. As far as we are aware (search through Entrez Pubmed), except for vitreopapillary traction associated with diffuse macular oedema, 16 this was not previously reported.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Extrafoveal traction sites are illustrated to be commonly associated with diffuse macular oedema. As far as we are aware (search through Entrez Pubmed), except for vitreopapillary traction associated with diffuse macular oedema, 16 this was not previously reported.…”
Section: Introductionmentioning
confidence: 92%
“…[13][14][15] In eyes with non-proliferative or proliferative diabetic retinopathy, it has been reported, using optical coherence tomography (OCT), that a vitreous traction at the optic nerve head (ONH) may result in diffuse oedema and/ or serous retinal detachment located between the ONH and the macula. 16 Pars plana vitrectomy (PPV) was found commonly beneficial in eyes with diffuse DME associated with vitreomacular traction. [17][18][19] The surgical outcome was variable in different studies if no vitreomacular traction was apparent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, high-resolution imaging techniques, mainly OCT, were found useful in the visualization of retinal anatomy with near microscopic resolution, [4][5][6][7][8][9][10] and new data have been found regarding LMH: (a) best-corrected visual acuity (BCVA) as low as 20/200, 20/400 and counting fingers at 8 feet was reported in eyes with LMHs; [11][12][13] (b) several studies showed persistent vitreous adherence to the edge of the LMH, baring a potential for traction and LMH progression; [13][14][15] (c) two reports showed an LMH in each that underwent spontaneous transition to a full-thickness macular hole; 9,13 and (d) pars plana vitrectomy (PPV) and gas tamponade for symptomatic LMH improved visual acuity in most eyes, provided that it included peeling of the internal limiting membrane (ILM). [11][12][13] All of the above seem to give rise to a revised concern about LMHs in regards to their morphologic abnormalities, natural history, potential of worsening, and the possibility of beneficial surgery with reversibility of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Vision may be adversely affected; recovery follows spontaneous/surgical relief of VPT. 3,4 However, the need for vitrectomy has been questioned, as VPT has not been conclusively shown to be the sole cause of visual decline.…”
mentioning
confidence: 99%